INDUSTRI RUMAHAN (HOME INDUSTRY) KERAJINAN TRADISONAL TANJAK DI DESA BATU AMPAR KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - Rizki Padli; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tanjak Traditional Home Industry (Home Industry) in Batu Ampar Village, Kemuning District, Indragiri Hilir Regency. The purpose of this study was to find out how social capital and the conditions that support and inhibit the development of the Malay tanjak industry in Batu Ampar Village, Kemuning District, Indragiri Hilir Regency. The theory used is the theory of social capital proposed by Coleman consisting of kepaan, networks, social networks, values and norms. This type of research uses a descriptive qualitative approach with a case study method. This sub-research consisted of 7 people consisting of entrepreneurs and consumers who participated in the traditional Malay tanjak craft business. The data sources used were primary data sources and secondary data. Data collected by data collection techniques in the form of observation (Observation) and Inteview interviews. Analysis of the data used in this study with data collection techniques from various sources by including the source of the theory used in accordance with the phenomenon of social phenomena The results of this study are very important social capital in a company engaged in small industry or. networks, beliefs and norms that play a very important role in the construction of traditional crafts in Batu Ampar Village, Kemuning District, Indragiri Hilir Regency. The network is a link that connects one individual to another or between groups with other groups, has a positive impact moreover in supporting the acquisition of raw materials and marketing of traditional tanjak Melayu handicraft businesses. Trust is the basis for the intertwining of relationships between actors. others in the world of commerce. Relations based on trust will create good conditions in trading activities. Social norms like ways. customs, rules and customs. Is a rule of social life behavior Keywords: Social Capital, Home Industry Craft Traditional Tanjak.